Proliferation, migration, and expression of oral-mucosal-healing-related genes by oral fibroblasts receiving low-level laser therapy after inflammatory cytokines challenge - Basso, Fernanda G. [UNESP]; Soares, Diana G. [UNESP]; Pansani, Taisa N. [UNESP]; Cardoso, Lais M. [UNESP]; Scheffel, Débora L. [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Wiley, 2016)
Background and Objectives: Increased expression of inflammatory cytokines in the oral cavity has been related to the etiopathogenesis of oral mucositis and to delayed oral mucosal repair. Low-level laser therapy (LLLT) stimulates proliferation and migration of gingival fibroblasts, but the effects of specific inflammatory cytokines on oral mucosal cells and the modulation of these effects by LLLT have not been fully investigated. Therefore, this study investigated the effects of LLLT on oral fibroblasts after being challenged by oral-mucositis-related inflammatory cytokines. Methods: Human gingival fibroblasts were seeded in plain culture medium (DMEM) containing 10% fetal bovine serum (FBS) for 24 hours. Then, cells were kept in contact with inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-8) in serum-free DMEM for 24 hours. After this period, cells were subjected to LLLT with a diode laser device (LaserTABLE, InGaAsP, 780 nm, 25 mW) delivering energy doses from 0.5 to 3 J/cm2. Irradiation was repeated for 3 consecutive days. Twenty-four hours after the last irradiation, cell migration (wound-healing and transwell migration assays), cell proliferation (BrdU), gene expression of COL-I and growth factors (real-time PCR), and synthesis of COL-I (Sirius Red assay) and VEGF (ELISA) were assessed. Data were subjected to two-way ANOVA and Tukey's tests or Kruskall–Walis and Mann–Whitney tests (P < 0.05). Results: The inflammatory cytokines decreased the migration capacity of gingival fibroblasts. However, a statistically significant difference was observed only for IL-6, detected by transwell assay, where 30% less cells migrated through the pores (P < 0.05) and IL-8, with an increased wound area (116%; P < 0.05), detected by the wound healing method. Cell proliferation was not affected by contact with cytokines, while growth factors and COL-I expression (approximately 80%; P < 0.05), as well as VEGF synthesis (approximately 20%; P < 0.05), were decreased after contact to all tested cytokines. The opposite was seen for total collagen synthesis. LLLT promoted an acceleration of fibroblast migration (30%; P < 0.05) and proliferation (112%; P < 0.05) when delivering 0.5 J/cm2 to the cells previously in contact with the inflammatory cytokines. Gene expression of VEGF (approximately 30%; P < 0.05), and EGF (17%; P < 0.05), was stimulated by LLLT after contact with TNF-α and IL-6. Conclusion: LLLT can counteract the negative effects of high concentrations of inflammatory cytokines, especially IL-6 and IL-8 on gingival fibroblast functions directly related to the wound-healing process. Lasers Surg. Med. 48:1006–1014, 2016. © 2016 Wiley Periodicals, Inc.
Keywords: cell proliferation; gene expression; mucositis; wound healing